What is the optimal dosing of lisinopril for renal protection in normotensive patients with diabetes and moderate albuminuria (30–299 mg/d)?. Issue 2 (February 2018) - Wilkie, Justin; Poch, Aaron L.
Abstract : EVIDENCED‐BASED ANSWER : Lisinopril dosed at least 10 mg daily decreases risk for progression from micro‐ to macroalbuminuria in patients with cardiovascular risk factors including diabetes (SOR: B, meta‐analysis of RCTs). In insulindependent patients with microalbuminuria, lisinopril 10 to 40 mg daily (titrated to lower diastolic pressures <75 mmHg) decreases albumin excretion rates (SOR: C, extrapolated from an RCT in which patients had normal‐range blood pressures and modest systolic hypertension).